2020
DOI: 10.3389/fnagi.2020.00120
|View full text |Cite
|
Sign up to set email alerts
|

Natural Reading in Parkinson’s Disease With and Without Mild Cognitive Impairment

Abstract: Background: Patients with Parkinson's disease (PD) show eye movement abnormalities and frequently complain about difficulties in reading. So far, it is unclear whether basal ganglia dysfunction or cognitive impairment has a greater impact on eye movements during reading.Objective: To analyze eye movement behavior during a natural reading task with respect to cognitive state and dopaminergic therapy in PD and healthy controls. Methods: Eye movements of 59 PD patients and 29 age-and education-matched healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…For example, a somewhat recent meta-analysis concluded that individuals with depression show reduced maintenance of gaze towards positive stimuli, and anxious individuals showed difficulty disengaging from threatening stimuli during visual search tasks [ 61 ]. Moreover, Stock et al [ 62 ] observed that individuals with PD fixate on words for a greater duration and make a greater number of regressions when reading. As these morbidities and alternative neurological disorders can independently influence naturalistic eye movement behaviours, if one were to analyse naturalistic eye movement behaviours in individuals with AD with these comorbidities, it would be difficult to parse apart the influence of AD from the influence of the comorbidity.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a somewhat recent meta-analysis concluded that individuals with depression show reduced maintenance of gaze towards positive stimuli, and anxious individuals showed difficulty disengaging from threatening stimuli during visual search tasks [ 61 ]. Moreover, Stock et al [ 62 ] observed that individuals with PD fixate on words for a greater duration and make a greater number of regressions when reading. As these morbidities and alternative neurological disorders can independently influence naturalistic eye movement behaviours, if one were to analyse naturalistic eye movement behaviours in individuals with AD with these comorbidities, it would be difficult to parse apart the influence of AD from the influence of the comorbidity.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] The challenge in measuring speech and voice parameters is that one needs to account for the added instability of the speech signal because of movement disorders such as tremors, dyskinesias, dystonic postures, possible attention/cognitive problems, and fatigue. Reading abilities may be compromised by visual or reading difficulties 21 ; the emotional burden can affect speech. 22 As external cues for loudness can alter the volume, speech should be recorded by an independent person in a room not associated with speech therapy and consistent, clear instructions should be provided.…”
mentioning
confidence: 99%
“…Wight and Miller (2015) reported a significant increase in SPL reading pre‐ to 12 months but not 24 months post‐treatment. Neurological and cognitive–linguistic factors which may have impacted SPL for reading in the current study include impaired comprehension of written material (Murray & Rutledge, 2014); slowness in psychomotor tasks (Broeders et al., 2013), and changes in eye movement in PD leading to reduced speed in reading and altered reading pattern (Stock et al., 2020). The significant decrease in SPL reading from 6 months post‐treatment highlights the importance of supporting PWPD to continue to read salient, functional material that is visually and cognitively appropriate for their changing abilities, from post‐LSVT LOUD onwards.…”
Section: Discussionmentioning
confidence: 91%